Drive - Fanney Sigurðardóttir 1985-; Helgi Rúnar Einarsson 1987-; Hrafn Orri Hrafnkelsson 1994-; Kristinn Þorri Þrastarson 1989- (2017)
This reports outlines the development and documentation of the project Drive. The project is a Final Project for the University of Reykjavik and is worked in collaboration with TM Software. TM Software had an interest in developing Drive as a part of a series of solutions for the travel industry. The team consists of four third-year students in the Computer-Science division of Reykjavik University. Fanney Sigurðardóttir, Helgi Rúnar Einarsson, Hrafn Orri Hrafnkelsson and Kristinn Þorri Þrastarson. The team has worked together for quite a while on other projects and have been very satisfied with the results. Therefore the team was confident when deciding to work together on this final project. Drive is a web application that will function as a dashboard and a vehicle fleet observation system. Car rentals and companies alike can be served with an overview of the current status of their fleet, as well as accumulated data over time. Car rental companies in Iceland do not monitor their vehicles after the customer is handed the keys and drives off. Most vehicle fleet management system are very expensive and require special permissions from the actual driver of the vehicle. Also, these systems mostly focus on lowering expenses for their customers by lowering gasoline consumption with route optimization. Solutions that do not factor into car rental companies expense structure. Drive focuses on giving accurate information about the car fleet's behaviour. Car rentals can then know if any cars are driving in forbidden areas, see the most popular stops as well as give their customers warnings about environmental changes in their surroundings. Drive is entering a new turf in an already established market here in Iceland. Trackwell respectively seems to have the largest part of the market, however Drive has a slightly different focus, which attracts new customers to the market.